Antimicrobial Use in Pig Farms in the Midwestern Region of Minas Gerais, Brazil - Bruno César de Oliveira; Idael Christiano de Almeida Santa Rosa; Maurício Cabral Dutra; Felipe Norberto Alves Ferreira; Andrea Micke Moreno; Luisa Zanolli Moreno; Júlia da Mata Góes Silva; Simone Koprowski Garcia; Dalton de Oliveira Fontes (MDPI AG, 2024)
The use of antimicrobials in swine production is an issue that concerns the whole world due to their impact on animal and public health. This study aimed to verify the antimicrobial use in 29 commercial full-cycle farms in the midwestern region of the state of Minas Gerais, since this region is a hub of intensive pig farming in Brazil, as well as the possible correlations between the use of antimicrobials, biosecurity, and productivity. A total of 28 different drugs used for preventive purposes were described. On average, the herds used seven drugs, exposing the piglets for 116 days and totaling 434.17 mg of antimicrobials per kilogram of pig produced. Just eight active ingredients made up 77.5% of the total number of drugs used on the studied herds. Significant differences were found between the variables, biosecurity score and number of sows, antimicrobial amount and number of drugs, number of drugs and number of sows, and between productivity and biosecurity scores. The use of antimicrobials was considered excessive in the swine farms in the state of Minas Gerais compared to what was reported in Brazil and in other countries. Educational measures and better control should be proposed to reduce the preventive use of antimicrobials.